IMPLEMENTASI TOTAL QUALITY MANAGEMENT UNTUK MENINGKATKAN KEUNGGULAN KOMPETITIF MADRASAH DI MA AL-AMIRIYAH DARUSSALAM - Amirudin Hamzah Has; Zulfi Zumala Dwi Andriani (Universitas Islam Negeri (UIN) Sumatera Utara, 2024)
This study aims to analyze in depth the implementation of Total Quality Management in increasing competitive advantage in MA Al-Amiriyah Darussalam. This research uses a qualitative approach of case study type in MA Al-Amiriyah Darussalam Banyuwangi, which was chosen because of its commitment in implementing Total Quality Management. Data were collected through in-depth interviews, participatory observation, and documentation, with purposive informants including the head of madrasah, deputy head of curriculum, head of administration, senior teachers, and chairman of the committee. Data analysis was done thematically through the stages of reduction, presentation, and conclusion drawing. Data validity was strengthened by triangulating sources and methods to understand the implementation of Total Quality Management and its contribution to increasing the madrasah's competitive advantage. The results of this study show that the successful implementation of Total Quality Management at MA Al-Amiriyah Darussalam is supported by three main factors: visionary leadership of the madrasah head who encourages a culture of quality and collective commitment; adaptive educational services through curriculum development, teacher training, and structured evaluation; and a consistent and data-based quality evaluation system. These three aspects synergize to form a strong foundation in maintaining the quality of education in a sustainable manner, making the madrasah more adaptive, responsive and competitive in facing the dynamics and demands of modern education.